β6 Integrin Subunit Deficiency Alleviates Lung Injury in a Mouse Model of Bronchopulmonary Dysplasia - Hogmalm, Anna (American Thoracic Society, 2010)
Pulmonary inflammation is associated with the development of bronchopulmonary dysplasia in premature infants. We have previously shown that perinatal pulmonary expression of human IL-1β is sufficient to cause a lung disease similar to bronchopulmonary dysplasia, characterized by inflammation, impaired alveolarization, poor postnatal growth, and increased mortality in infant mice. The αvβ6 integrin plays a critical role in regulating inflammation in the adult lung. To study the role of the β6 integrin subunit in neonatal inflammatory lung disease, we compared the pulmonary development in IL-1β–expressing infant mice with wild-type or null β6 integrin loci. Absence of the β6 integrin subunit decreased the mortality and improved the postnatal growth of IL-1β–expressing pups. The disrupted alveolar development of IL-1β–expressing mice was improved by β6 integrin deficiency. IL-1β–expressing β6(−/−) pups had shorter alveolar chord length and thinner alveolar walls than IL-1β–expressing β6(+/+) pups. In addition, the absence of the β6 integrin subunit reduced IL-1β–induced neutrophil and macrophage infiltration into the alveolar spaces. β6 integrin subunit deficiency suppressed inflammation and goblet cell hyperplasia in the airways and alleviated airway remodeling in IL-1β–expressing mice. The expression of the chemoattractant proteins, keratinocyte-derived chemokine, macrophage-inflammatory protein–2, calgranulin A, and calgranulin B, of osteopontin, and of the chitinase-like lectins, Ym1 and Ym2, was lower in IL-1β–expressing β6(−/−) than in IL-1β–expressing β6(+/+) mice. We conclude that absence of the β6 integrin subunit protects the infant murine lung against IL-1β–induced inflammation and injury.